THE IMPLEMENTING PROBLEM-BASED LEARNING IN LITERACY-ORIENTED CLASSROOMS TO ENHANCE STUDENTS’ CRITICAL READING AND WRITING ENGAGEMENT - Syahrul Riza; Maidar Maidar (SENSEI RESEARCH CENTER, 2023)
Literacy-oriented classrooms require instructional practices that enable students to read critically, interpret information, negotiate meaning, construct arguments, and communicate ideas through written and oral responses. However, many literacy lessons remain teacher-centered and text-reproduction oriented, limiting students’ opportunities to question, investigate, collaborate, and solve authentic literacy problems. This study examined the implementation of Problem-Based Learning in literacy-oriented classrooms and investigated its effect on students’ critical reading and writing engagement. A mixed-method quasi-experimental embedded design was employed involving 96 senior high school students divided into an experimental group and a control group. The experimental group received literacy instruction through Problem-Based Learning, while the control group received conventional text-based instruction. Data were collected through literacy performance tests, classroom observation, student reflective journals, interviews, and learning artifacts. Quantitative data were analyzed using descriptive statistics, paired-sample t-tests, independent-sample t-tests, normalized gain, and effect size. Qualitative data were analyzed thematically. The findings showed that students in the Problem-Based Learning classroom achieved significantly higher literacy performance than those in the conventional classroom. The strongest improvements occurred in problem identification, evidence-based reading, argument construction, and collaborative discussion. The study concludes that Problem-Based Learning can strengthen literacy-oriented classrooms when authentic problems, rich texts, inquiry scaffolds, collaborative tasks, and reflective writing are systematically integrated.